El Salón de Reinos del Palacio del Buen Retiro como espacio teatral - Javier Rubiera (Mélanges de la Casa de Velázquez, 2025)
This article begins a study of the functions of the “Salón de Reinos” as a theatrical space in the Buen Retiro Palace since its construction in Madrid around 1633. It begins by recalling that the Great Hall or Hall of Realms of the Buen Retiro Palace was already conceived with the intention of hosting palace festivities, among them, theatrical performances, presided over by the monarchs. Some terminological clarifications are made regarding the different names of the Salón, taking into account its possible relationship with other names such as “saloncete” and “saloncillo”, which are widely used in seventeenth-century documentation. After some observations on its theatrical use between 1650 and 1700, the final part of the article focuses on the space of the Salón from the perspective of the movement of stages and stage machinery in the court environment of the seventeenth century, both in the Alcázar of Madrid and in the Buen Retiro Palace.